2007
DOI: 10.1038/sj.mp.4002081
|View full text |Cite
|
Sign up to set email alerts
|

Increased serotonin 2C receptor mRNA editing: a possible risk factor for suicide

Abstract: Suicide is a major public health problem with B1 million victims each year worldwide. Up to 90% of adults who commit suicide have at least one psychiatric diagnosis such as major depression, bipolar disorder (BPD), schizophrenia (SZ), substance abuse or dependence. A question that has remained unanswered is whether the biological substrates of suicide are distinct from those of the psychiatric disorders in which it occurs. The serotonin 2C receptor (5-HT 2C R) has been implicated in depression and suicide. We,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 49 publications
9
70
2
Order By: Relevance
“…[32][33][34]39,47 Consistent with them, we also confirmed that reduced expression level of HTR2C did not affect editing level in brains of patients. Therefore, expression level of HTR2C is not likely to affect RNA editing level in brains of patients with mental disorders.…”
Section: Effect Of Genetic Variations Of Adars On Htr2c Rna Editingsupporting
confidence: 76%
See 1 more Smart Citation
“…[32][33][34]39,47 Consistent with them, we also confirmed that reduced expression level of HTR2C did not affect editing level in brains of patients. Therefore, expression level of HTR2C is not likely to affect RNA editing level in brains of patients with mental disorders.…”
Section: Effect Of Genetic Variations Of Adars On Htr2c Rna Editingsupporting
confidence: 76%
“…33 Recently, Dracheva et al examined RNA editing status in SZ and BD using different cohorts. 32 Although they again did not find editing alterations in patients with SZ, they detected significant decrease of VGV isoform in BD. Moreover, they provide further evidence of association of altered RNA editing and suicide.…”
Section: Effect Of Genetic Variations Of Htr2c On Expression and Rna mentioning
confidence: 99%
“…24,27 Later studies demonstrated an association between 5-HT 2C R editing and suicide. [23][24][25][26] In particular, one study conducted in our laboratory, which used samples from the same cohort and brain region as the present study, showed that the specimens from individuals who had committed suicide displayed greater 5-HT 2C R editing than those from individuals who died from other causes, regardless of psychiatric diagnosis. 26 One could hypothesize that if these differences in editing were the result of greater ADAR activity in suicide completers, the editing efficiency of other ADAR substrates would also be elevated in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In addition, editing of another neurotransmitter receptor, the serotonin 2C receptor (5-HT 2C R), has been implicated in schizophrenia, depression and suicide. [23][24][25][26][27][28] However, editing in iGluRs has never been comprehensively assessed in the human brain in the context of psychiatric conditions within the same brain region.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,19,29,30 The editing of A-to-I positions in the 5-HT 2c receptor was observed to increase in the victims of suicide among patients with depression or schizophrenia, thus suggesting that 5-HT 2c receptor mRNA editing may be associated with changes in mood but not with comorbid psychiatric illnesses. 31 Indeed, the extent of RNA editing at these sites differs among mouse strains and was altered after the administration of antidepressants or exposure to a stressful environment in normal mouse brains. 16,32,33 An A-to-I conversion of glutamate receptor subunits markedly alters the channel properties of glutamate receptors and hence, the neuronal excitability as a whole.…”
mentioning
confidence: 99%